Key Research Areas in Territorial Marketing from 2020 to 2025 - Sztuk, Aleksandra (Kluczowe obszary badawcze w marketingu terytorialnym w latach 2020-2025, 2025)
Aim: The paper aims to present the identified key research areas in territorial marketing in 2020-2025. Methodology: To identify relevant research materials, a literature analysis was conducted using the licensed database, the Web of Science. The keywords used for the search included territorial marketing and place marketing, as inserted by the authors. The analysis focused on articles published between 2020 and 2025 and only included materials written in English. Keywords that appeared at least three times were selected for the mapping process. Ultimately, 66 distinct keywords were identified, which formed five clusters representing different research areas. Results: Based on the conducted mapping, key research areas in territorial marketing were identified and named, focusing on image communication and building the city’s brand in recent years. The research indicates that this process should be based to a greater extent on distinguishing features referring to the identity of the place. Another important and current research trend is the analysis of marketing activities aimed at migrants, including digital nomads – temporary workers who often change location. Implications and recommendations: This paper presents recommendations for three directions of future empirical research, the results of which can provide important data supporting the development of current research areas in territorial marketing. Originality/value: Developing a synthetic review of contemporary issues related to place marketing enables scientists to identify key research problems. The systematic analysis of evolving issues facilitates the consolidation of knowledge and supports the dynamic development of this field, contributing to the improvement of place marketing strategies.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 1, s. 109-117
Keywords: territorial marketing; place marketing; VOSviewer; city image; digital nomads; marketing terytorialny; merketing miejsc; wizerunek miasta; cyfrowi nomadzi